A Hidden Lymphoma With Unusual Cutaneous Silence - Imran Naeem Aziz; Muhammad Tayyab Anwar; Vaishali Deenadayalan; Maryam Fatima Zia; Vinod Solipuram; Shiraz Fidai; Ayesha Junaid Zaidi; Arfa Imran; Mona Dasgupta (Annals of Internal Medicine: Clinical Cases)
Subcutaneous panniculitis-like T-cell lymphoma is a rare and challenging diagnosis and has emerged as a distinct entity over the past 3 decades. Traditionally characterized by skin lesions, it represents an anomaly in our recent case, where the lymphoma manifested solely within the peritoneum, devoid of any discernible skin findings.